Impacts of covid-19 pandemic on Komárom-Esztergom county’s economy via case study of several automotive companies in 2020 - Peredy, Zoltán; Vörös, Mihály; Péli, László (Studia Mundi – Economica, 2021)
One of the strategic economic sector in Komárom-Esztergom county (KEM) is the automotive industry, which currently faces structural transformation. The possible reasons beyond this one can be the rise of different electric drive systems, emerging labor shortages due to negative demographic trends, and the unfavourable economic impacts caused by “COVID-19” pandemic on production, investments, and supply chain. Due to these difficulties, those processes started to speed up which closely linked to Industry 4.0. global trends including application of process[1]related automation, robotics, digitization, artificial intelligence.Independently from the coronavirus, an adjustment process has begun among county firms, repositioning their production, rethinking workforce capacity, production chain structure, and inventory policy. Presumably, these contributed to address the challenges as consequences of the negative effects of the COVID-19 epidemic without major shocks. This case study provides an overview on the implemented solutions used by some selected automotive companies (original equipment manufacturer -OEM, first level supplier TIER1 and local, Hungarian[1]owned small and medium-sized enterprises) to overcome the difficulties caused by the epidemic. The economic recession caused by the coronavirus (due to real economic and money market uncertainties) resulted a minor “slow-down” in the county’s economy but flexibility, creativity helped companies to survival.However, creativity can not be integrated on system level into multisegment that decompose the production processes into operations, operational elements, steps and running them according to strict, internationally standardized protocols. Instead of OEM or TIER1, it would be worthwhile to attract into the county smaller, second level suppliers - the TIER2 - (a detailed list should be made about them). The innovation processes take place in the automotive industry neither at the OEM nor TIER1 units here, but in their second or third round suppliers. Hungarian original ideas can be commercialised in this corporate segment.